Endoscopic Removal of an Uncommon Iatrogenic Foreign Body from the Maxillary Sinus: A Dental Burr - Nafil Arimbrathodi; Waqar Aslam; Abhishek Menon; Ali Ahmad Al Saadi (Case Reports in Otolaryngology)
Instrument fracture during procedure is not uncommon for dental surgeons, especially in root canal surgeries, usually inside the root canals. In rare instances, high-speed rotary instruments can be fractured and can be dislodged in key anatomical areas of face. In our case report, a high-speed dental burr most probably penetrated the root and was seen in the left maxillary sinus during a likely routine dental procedure. The work-up and endoscopic surgical management of the case is described. Practitioners should be in great care during dental procedures and endodontic treatment to avoid unexpected complications by introducing foreign bodies into maxillary sinus. Any patient presenting with recurrent unilateral facial pain or unilateral sinus symptoms with/without previous history of sinusitis should raise the suspect of a foreign body in the paranasal sinus regardless of any previous history of dental procedure.